The potentialities of Chinese airline market for Lisbon international airport: the empirical modelling analysis - Vicente, José (2012)
In this paper we propose a comparative analysis between an empirical gravity model and a dynamic regression model with the objective to explain the potentialities of the Chinese airline market for Lisbon International Airport (air passengers demand). We confirm the viability to create some direct flights from Lisbon International Airport to Chinese airline market, with the strategy to attract the transfer passengers flow with origin on Latin America. Panel dada is used to determine the influence of the explanatory variables, on average number of passengers (air passengers demand). The results are creating by the Stata final outputs. We also demonstrate that the dynamic regression model used in this paper is more robust and better than the empirical gravity model, often considered as a reference method in the field of aviation. The most relevant variables on the dynamic regression model are PPP (gross national income (GNI) converted to international dollars using purchasing power parity rates), Business and Trade Factor, and Tourism and Cultural Factor. Furthermore, we find some possible explanations for the results.